Who Benefits from Dual Training Systems? : Evidence from the Philippines - Igarashi, Takiko; Acosta, Pablo (World Bank, Washington, DC, 2018)
Rising youth unemployment rates have been increasingly recognized as a serious challenge in developing and advanced economies, as the trend indicates a potential skills gap between the demands of the workforce and recent graduates. Effective dual education programs utilizing a combination of classroom instruction and practical skill training present an approach to developing a skilled workforce and meeting workforce demands. To evaluate the impact of the Philippine Dual Training System on labor market outcomes, this paper analyzes data from a recent survey tracking graduates from the Dual Training System and regular vocational training programs provided by technical vocational training institutes. The data analysis reveals that the Dual Training System has a significantly higher rate of return on labor market earnings compared with regular, classroom-only vocational training programs, particularly among high school graduates who did not perform well academically during basic education. The magnitude of the impact of the Dual Training System is also likely to increase in correlation with the intensity of the on-the-job component.